(untitled) (Journal of the College of Basic Education, 2022)
It was reported on the authority of Imam Ali bin Al-Hussein, may God’s prayers be upon him, that he said: ((The verses of the Qur’an are treasures, so whenever you open a treasury, you should look at what is in it)).This research searches the treasury of the blessed Surat Al-Dukhan and scrutinizes it. Surat Al-Dukhan, with its short verses, close rhymes, and violent images, touches the strings of hearts and simulates souls in a miraculous Quranic style and intentional artistic expression.And the beauty of its cohesion, so the research focuses in its path from its beginning to its end on explaining the coherence and harmony in the context of the surah and its expressive means and influences that awaken the human heart to receive these living, pulsating realities.He studies the Qur’anic text, starting with the individual and its synonyms, nominal or verbal, and looks at the aspects of Qur’anic composition such as: introduction, delay, deletion, remembrance, reversal, definition, negation, proportionality,